New Approaches to Individual Instrumental Tuition in Music Education - Anastasia Hasikou (Athens Institute for Education and Research, 2020)
Individual instrumental tuition has been the focus of some new research in musical scholarship during the last two decades. The main conclusions that appear to be shared by scholars in this field such as Gerald Jones, Knud Illeris, John Heron, Andrea Creech and Helena Gaunt is that a combination of modern social circumstances together with rapidly advancing technological innovations have considerably widened accessibility to music experience of different kinds and as a consequence has affected individual instrumental tuition. Based on a considerable analysis of new teaching approaches to individual tuition on a conservatoire level, this paper will endeavor to suggest that the traditional mode of instrumental tuition, which encompasses a hierarchy and mostly directive mode of teaching, has shifted significantly towards a responsive mode of teaching and a more autonomous, self-directed mode of learning. This paper will conclude with a consensus that one-to-one instrumental tuition is shifting dramatically and new approaches whose aim is to facilitate the best possible learning outcomes need to be taken into consideration by music instrumental tutors.